Zomromcom - Dade, Olivia (Supernatural entanglements, 2025)
"When Eden "Edie" Brandstrup attempts to save her sweet, seemingly harmless human neighbor from the first major zombie breach in two decades, she's stunned to be saved by him--and his ridiculously large sword--instead. As it turns out, he's actually a super-old, super-surly vampire. But for all her neighbor's newly revealed cynicism and lethality, Gaston "Max" Boucher (yes, Gaston) is unexpectedly protective. He wants her to stay in his safety bunker until the breach is resolved. Edie can't risk more innocent people getting killed, though--and Max won't let her save them alone. As they unravel a sinister conspiracy to set zombies loose on the world (again), the duo meet a host of lovable allies and discover they're not the only ones willing to fight for the future of humanity. Despite the awful timing, Edie finds herself falling for the vampire who's helping her save the world . . . but all their dangerous plans could end their future before it even begins. As she and Max battle side by side, Edie is forced to consider whether having a love worth living for also means having a love you'd die for--and, in a world that grows deadlier by the minute, whether that's a risk she's willing to take"--